Konvergensi dan Divergensi Bahasa dalam Interaksi Pedagang dan Pembeli di Pasar Jadi Mesari, Tabanan - Made Ratih Parwati, Pande; Made Dhanawaty, Ni; Putu N. Widarsini, Ni (CV. Ulil Albab Corp, 2023)
The purpose of this study is to determine the process of convergence and divergence in the interaction of traders and buyers at Pasar Jadi Mesari, Tabanan, to determine the mastery of the language of traders and buyers in the surrounding environment at Pasar Jadi Mesari, Tabanan, to find out what factors cause convergence and divergence to occur. in the interaction of traders and buyers at the Jadi Mesari Market, Tabanan. This study uses sociolinguistic theory, namely language accommodation proposed by Giles & Coupland (1991) and other sociolinguistic theories as support, namely the realm of language use, language choice, speech components, code switching, code mixing and interference. This research uses the primary data of this study, namely in the form of speech used in interactions between traders and buyers at the Jadi Mesari market, Tabanan.. The analytical method used to analyze the data is a qualitative descriptive method. Qualitative descriptive research methods are often used to analyze events, phenomena or situations socially. The agiv method has a specifier part of the language itself. The results of this study are two language choices used by traders and buyers, namely Balinese and Javanese. There are 10 data showing convergence and 5 data showing divergence. Factors that influence language consist of time, place, socio-culture, situation, medium of expression, and age and gender.